Incidencia del primer respondiente y primera autoridad respondiente en la investigación criminal (2014)
So the development of the activities is given to run by judicial police it is necessary that it be informed that he was committed the punishable; This we call criminal news and this is knowledge or information obtained by police or police surveillance, in relation to the realization of one or more behaviors that set up a crime. You can have knowledge of it half written, verbal and can also be through denunciation, complaint, special request by the Attorney General of the nation, by telephone calls, News reported by the media of communication, anonymous, informants, electronic mail, among others. At this stage should be collected the various interviews achieved getting possible witnesses of the fact; Likewise perform the correct collection, packing and labeling of the material evidence and physical evidence found at the scene, in order to thus comply with the chain of custody, guaranteeing the assurance of these conservation, and its consequent validity within the research